Reflective Evaluation after Investigating EFL Students’ Preferences on the Genres of Essay Writing at Final Examination: A Two Semesters Study - Syayid Sandi Sukandi (UICELL, 2019)
One of the required tasks of being an English lecturer in Indonesia is to perform assessment and evaluation after teaching in a one-semester course. The learning of English essay writing seems to be important for all majors. After collecting actual data from Indonesian EFL students taking an English essay writing course in the even semester of 2015/2016 and 2016/2017, it was found that the students had a certain pattern of interest to which genre they might prefer to write in their final examination. A convenient sampling technique was applied in this research. In terms of data, 71 students enrolled in the course in 2015/2016 (Group 1) and 75 students enrolled in the 2016/2017 (Group 2) academic year. The highest preferred genre for Group 1 was comparison-contrast with 28% and Descriptive for Group 2 with 33%. Meanwhile, the lowest preferred genre for Group 1 was Argumentative with 11% and Narrative for Group 2 with 9%. By looking at these percentages, a few pedagogical reflective evaluations can be made. Hopefully, one question that may be raised for all English teachers and lecturers in Indonesia: “Have we considered EFL students’ interests before evaluating their overall performance on our essay writing course?" Keywords: Assessment, Essay, Evaluation, Pedagogy, Writing